2017
DOI: 10.1590/s1678-9946201759082
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal parasitic infections among expatriate workers in various occupations in Sharjah, United Arab Emirates

Abstract: Intestinal parasitic infections are prevalent throughout many countries. This study aimed to determine the prevalence of intestinal parasite carriers among 21,347 expatriate workers, including food handlers and housemaids attending the public health center laboratory in Sharjah, UAE. Stool sample collection was performed throughout the period between January and December 2013. All samples were examined microscopically. Demographic data were also obtained and analyzed. Intestinal parasites were found in 3.3% (7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 18 publications
2
13
0
Order By: Relevance
“…The authors found intestinal parasitic infections in 3.3% of the sample and, among these, 96% were positive for a single parasite, such as Giardia (36%) and Entamoeba histolytica (31%). Infections were positively correlated with gender (male workers) and with the occupational category (mostly workers in the food and agriculture industries) [19]. Percentages of higher intestinal infections among migrant workers were also found in the study of Taha and colleagues, with higher infections among farmers (20.6%) followed by food handlers (18.8%), shepherds (17.8%), drivers (13.4%) and domestic (13.3%).…”
Section: Infectious Diseasessupporting
confidence: 52%
“…The authors found intestinal parasitic infections in 3.3% of the sample and, among these, 96% were positive for a single parasite, such as Giardia (36%) and Entamoeba histolytica (31%). Infections were positively correlated with gender (male workers) and with the occupational category (mostly workers in the food and agriculture industries) [19]. Percentages of higher intestinal infections among migrant workers were also found in the study of Taha and colleagues, with higher infections among farmers (20.6%) followed by food handlers (18.8%), shepherds (17.8%), drivers (13.4%) and domestic (13.3%).…”
Section: Infectious Diseasessupporting
confidence: 52%
“…However, fitting univariate models does not allow the influence of confounding factors and their interactions to be identified, so in the second phase of our analysis we fitted all the significant effects from phase 1 into multifactorial models and combined these with age class and region of origin, which had been shown in our earlier paper to have had an influence on parasitic infections in these same individuals (14).This showed that many of the factors identified by univariate analysis are likely to have arisen through confounding interactions between fitted factors. The minimum sufficient models thus generated showed that the prevalence of combined helminth infections was influenced only by An earlier study conducted in Sharjah investigated intestinal protozoan infection rates among both expatriates and locals, and the infection rate was reported as 7.7% (17). The prevelance of protozoan infection in our study was higher at 11.7%.…”
Section: Discussionmentioning
confidence: 43%
“…The prevalence of the tested IPs was higher among workers with an educational attainment of grade 5 or below, from Asian countries, were living in rural settings in their home country, currently living in labour accommodation, sharing the same bedroom with ≥ 6 other workers, or sharing the same toilet with > 5 other people. The microscopically observed overall prevalence (17.4%) of at least one of the identified IPs in the surveyed expatriate workers is 5.3-times higher than that observed in expatriate workers in Sharjah Emirate (UAE) in 2008 [40] and 2013 [36]. This prevalence is slightly higher than that reported in expatriates working in Saudi Arabia (14.9%) in 2013 [41].…”
Section: Discussionmentioning
confidence: 83%
“…In 1982, the Abu Dhabi Public Health Preventative Medicine Laboratory found that 34% of all expatriate food handlers working in the country had helminths and protozoan infections [35]. A retrospective analysis of stool samples collected from a convenient sample of healthy expatriate workers for routine residency visa health screening between January and December 2013 reported that 3.3% of 21,347 tested expatriate workers of different occupations were positive for IPs in the emirate of Sharjah (UAE); however, the stool samples were only analyzed microscopically without molecular identification [36].…”
Section: Introductionmentioning
confidence: 99%